Entre o alinhamento frustrado e a busca de maior autonomia. As relações da Argentina com os Estados Unidos nos anos pós-Kirchner (2016-2021) - Bodemer, Klaus (2022)
Starting from the heavy historical legacy of relations between Argentina and the US, the main objective of this article is to analyse the development of these relations during the post-Kircher years 2016-2021. The analytical concepts used are neorealism, relative autonomy and intermestic policy, respectively „two level game“. At the operational level, the focus is on three areas: economic relations (trade and investment); security and defence policy y, thirdly, the impact of the new player on the Argentine chessboard, China, on bilateral relations. Finally, we analyse the development of bilateral relations during the first year of Joe Biden‘s presidency from the perspective of ‚active non-alignment‘, a new strategic proposal developed by a small group of foreign policy experts. Our analysis shows that relations between Argentina and the US, already from their asymmetric origins, are during the post-Kirchner years an eloquent example of intermestic policy, which meant that both Argentina‘s close alignment with the US under Macri‘s presidency and attempts towards greater autonomy through diversification under his successor Fernández had only modest successes. Pursuing a foreign policy of ‚active non-alignment‘ remains a challenge for Argentina that requires great diplomatic skill and whose success is by no means guaranteed thanks to a series of domestic and external impediments.